The Affordance Analysis of Teaching Chinese as a Second Language in an online Context - Wu Cai, PeiLing Wei (Forest Chemicals Review)
Based on the theory of affordance and empirical research, this study analyzes the good affordances of online Chinese as a second language (CSL) teaching via the software of VooV Meeting and Wechat which are not restricted by time and space, rich learning resources, online recording courses, increase participation methods, real-time learning feedback, synchronization and group guidance, learning task management, and improved learning efficiency. On the other hand, online CSL teaching via the software of VooV Meeting and Wechat also has the following bad affordances, such as issues of jet lag, lack of learning evaluation tools, lack of communication with school administrators, lack of financial support, and lack of a target language learning environment. This research proposes solutions for improving online learning outcome, namely constructing a complete online management system for learners of CSL, construct a psychological counseling system for learners of CSL and create a technical support system for online CSL teaching.